165 Urinary trimethyltin reflects blood trimethyltin in scrap recycling workers. (24th April 2018) - Ichihara, G; Iida, M; Fujie, T; Kaji, T; Kim, Y
Abstract : Introduction: We recently reported cases of scrap recycling workers intoxicated with organotin, who showed severe encephalopathy with symptoms of memory disturbance. The study showed higher ratio of urinary trimethyltin to urinary dimethyltin in the workers than that in the previous cases exposed to only dimethyltin, suggesting co-exposure to dimethyltin and trimethyltin in the present cases. The present study subsequently investigated blood dimethyltin and trimethyltin to understand the relationship of urinary and blood dimethlytin/trimethyltin for evaluation of validity of them as exposure markers for organotin. Methods: Urinary and blood dimethyltin and trimethyltin at different time points in three workers were measured with HPLC-ICP/MS. Regression analyses were conducted with independent values of blood dimethyltin and trimethyltin and dependent values of urinary dimethyltin and trimethyltin respectively. Multiple regression analysis with dummy variable of individual was also conducted for adjustment of individual factors. Result: Regression analysis showed significantly positive relation of urinary trimethyltin to blood trimethyltin, but did not show significant relation of urinary dimethyltin to blood dimethyltin. Multiple regression analysis with individual factor also showed significantly positive relation of urinary trimethyltin to blood dimethyltin. Discussion: The study shows that urinary trimethyltin reflects blood trimethyltin. In co-exposure to trimethytin and dimethyltin, urinary trimethyltin can be an internal exposure marker of trimethyltin, which is considered to be not only derived from external exposure to trimethyltin but also the trimethyl tin converted from dimethyltin, in human body.